The impact of flipped classroom model on EFL learners' academic achievement, attitudes and self-efficacy beliefs: A mixed method study - İyitoğlu, Orhan (My University, 2018)
The unprecedented pace of technology has inevitably manifested itself on practices and organization of the educational processes shaping not only the bridges of interaction that students build between themselves and their teachers but also the way they learn. As a response to the advent of new technology and the needs of these digital native students who grow up communicating through different means of technology, flipped classroom model has emerged as a form of blended learning that exploits the benefits of technology, constructivism, collaborative, distance learning and differentiated instruction by reversing the sequence of in and out of classroom procedures. Grounded in a mixed method embedded design, the study has taken a distinctive step to explore the quality and efficiency of flipped classroom model in enhancing university prep students' overall academic performance in EFL and that in its sub-skills, retention of that performance, attitudes toward and self-efficacy beliefs in EFL. Quantitative data was gathered through the administration of EFL Achievement Test, Attitudes toward EFL and Self-Efficacy Beliefs in EFL scales to 41 EFL students enrolled at Foreign Language School, Gebze Technical University in two different classrooms randomly assigned as experimental (N= 21) and control group (N=20). The intervention lasted during the whole 2016-2017 fall term. On the other hand, qualitative data was collected through follow-up semi-controlled interviews with 9 experiment group students from different achievement groups. All the quantitative data was analyzed using SPSS 21 for Windows, LISREL 8.54 for Windows and ITEMAN4 while qualitative data was analyzed manually by employing content analysis procedures. Findings of the study revealed flipped classroom as a teaching model significantly more effective than traditional lecture based instruction in enhancing EFL performance, long-term retention of this performance and improving its two vigorous predictors, attitudes toward and self-efficacy beliefs in EFL in higher education in Turkey. This facilitating role of flipped classroom model was also verified by qualitative results. To conclude, delving into the important dynamics of EFL performance in Turkey, the present study has promised a bulk of valuable results that set flipping EFL classrooms as an efficient way of dealing with failure in EFL in Turkey.

Teknolojinin baş döndürücü bir hızla gelişmesi sadece öğrencilerin birbirleri ve öğretmenleri ile iletişim kurma yöntemlerini değil ayrıca öğrenme biçimlerini de şekillendirerek eğitim uygulamalarında ve düzenlenmesinde kaçınılmaz olarak kendisini göstermektedir. Teknolojinin yeni boyutlarının ortaya çıkması ve teknolojinin farklı kanallarıyla iletişim kurarak büyüyen dijital açıdan yerli olan öğrencilerin ihtiyaçlarına karşılık olarak, ters yüz sınıf yöntemi teknolojiden, yapılandırmacılıktan, işbirlikçi öğrenme, uzaktan eğitim ve farklılaştırılmış öğretim yöntem ve yaklaşımlarından yararlanan, sınıf içi ve dışı prosedürlerini tersine çeviren bir çeşit harmanlanmış öğrenme modelidir. Karma gömülü desene dayanan bu çalışma ters yüz sınıf yönteminin hazırlık öğrencilerinin yabancı dil olarak İngilizce öğrenmede genel performanslarıyla birlikte alt boyutlarındaki başarılarını, bu performansın kalıcılığını artırmadaki ve İngilizce öğrenmeye karşı tutum ve öz yeterlik inançlarını geliştirmedeki etkililiğini ve kalitesini ortaya koymayı amaçlamıştır. Çalışmanın nicel verileri İngilizce Başarı Testi, İngilizce Dersine Yönelik Tutum ve İngilizce ile İlgili Özyeterlik İnancı Ölçekleri’nin Gebze Teknik Üniversitesi Yabancı Dil Okulu’nda okuyan 41 öğrenciye uygulanması ile toplamıştır. Bu öğrenciler çalışmanın değişkenleri açısından eşit olan iki sınıf rastgele deney (N= 21) ve kontrol grubu (N=20) olarak seçilmiştir. Bu deneysel uygulama 2016-2017 güz dönemi boyunca devam etmiştir. Öte yandan, çalışmanın nitel veriler deney grubunda farklı performans gösteren 9 öğrenci le yapılan yarı yapılandırılmış görüşmelerden elde edilmiştir. Toplanan tüm nicel veriler SPSS 21, LISREL 8.54 ve ITEMAN4 programları kullanılarak nitel veriler de el ile içerik analizi yöntemi kullanılarak analiz edilmiştir. Çalışmanın sonuçları ters yüz sınıf yönteminin düz anlatıma dayalı öğretim yapılan geleneksel sınıftan Türkiye ‘de yüksek öğretim kurumlarında İngilizce başarısını artırmada, bu başarının kalıcılığını sağlamada ve bu performansın iki güçlü belirleyicisi olan tutum ve özyeterliliği geliştirmede daha etkili olduğunu ortaya koymuştur.Ters yüz sınıf yönetiminin bu anlamlı etkisi nitel sonuçlarla da desteklenmiştir. Sonuç olarak, Türkiye’de yabancı dil olarak İngilizce öğrenme dinamiklerinin derinine inen bu çalışmada, ters yüz sınıf yöntemini Türkiye’de İngilizce öğrenme konusundaki başarısızlıkla mücadele etmede etkili bir yol olarak dikkate alınması gereken sonuçlar paylaşılmıştır.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2018
Keywords: Yabancı dil olarak İngilizce öğrenme başarısı; Harmanlanmış öğrenme; Ters yüz sınıf yöntemi; Özyeterlilik inançları; Academic achievement in EFL; Blended learning; Flipped classroom model; Self-efficacy beliefs